Utilization of a multidisciplinary team to reduce the rate of hospital readmissions in high‐risk heart failure patients at a community teaching hospital: The pharmacist's role in transitions of care. Issue 3 (11th January 2019) - Thurston, Maria M.; Liao, Tze‐chun Vivian; Lim, Tanna; Pounds, Teresa; Moye‐Dickerson, Pamela M.
Abstract : Introduction: Since the implementation of the Hospital Readmission Reduction Program, health systems have been working to reduce hospital readmission rates of patients with heart failure (HF). Of these efforts, the interventions with a multidisciplinary, multicomponent approach have lowered readmission rates as well as improved patient care, patient adherence, and patient outcomes. Objectives: The primary objective of this study was to determine if the addition of a pharmacist to the Transitional Care Team (TCT) would decrease the number of high‐risk HF patients readmitted to the hospital before 30 days. Secondarily, this study assessed the change in self‐reported medication adherence. Methods: This study was conducted at a community teaching hospital. A retrospective chart review was performed to identify HF patients who were at high risk for readmission admitted to the hospital from May 2012 to October 2013, as the historical control group. The intervention group included high‐risk patients with HF admitted from May 2014 to October 2015, who received the pharmacist‐led intervention during hospitalization and postdischarge. The pharmacist‐led intervention comprised five components: medication reconciliation, medication cost/formulary review, medication discharge counseling, providing and educating patients regarding self‐monitoring resources and postdischarge telephone follow‐up. The 8‐item Morisky Medication Adherence Scale was used to measure patients' self‐reported medication adherence at baseline, then 30 days after discharge. Results: The pharmacist‐led intervention assisted in decreasing the readmission rate from 33.7% in the historical control group to 21.3% in the intervention group with a relative risk reduction of 0.696 (confidence interval: 0.488‐0.994). There was also a significant improvement in self‐reported patient medication adherence scores. Conclusion: The addition of a pharmacist to the TCT that managed HF patients was associated with a decrease in the readmission rate for patients who were at high risk of readmission and improved self‐reported patient medication adherence.